2021
DOI: 10.1097/rlu.0000000000003785
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Multiparametric Functional Imaging to Assess Peritoneal Tumor Burden in Ovarian Cancer

Abstract: Purpose The aim of the study was to evaluate the clinical utility of pretreatment 18F-FDG PET/CT with quantitative evaluation of peritoneal metabolic cartography in relation to staging laparoscopy for ovarian carcinomatosis. Patients and Methods A retrospective review of prospectively collected data from 84 patients with FIGO (International Federation of Gynecology and Obstetrics) stage IIIC to IV ovarian cancer was carried out. All patients had a doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…A recently published study by Mallet et al 8 assessed the clinical utility of pretreatment 2- 18 F-FDG PET/CT applying a quantitative evaluation of peritoneal metabolic mapping compared with laparoscopic staging in ovarian cancer patients with peritoneal carcinomatosis as the primary objective. The secondary objective of this study was to analyze the performance of 2- 18 F-FDG PET/CT for detecting extra-abdominal metastases.…”
mentioning
confidence: 99%
“…A recently published study by Mallet et al 8 assessed the clinical utility of pretreatment 2- 18 F-FDG PET/CT applying a quantitative evaluation of peritoneal metabolic mapping compared with laparoscopic staging in ovarian cancer patients with peritoneal carcinomatosis as the primary objective. The secondary objective of this study was to analyze the performance of 2- 18 F-FDG PET/CT for detecting extra-abdominal metastases.…”
mentioning
confidence: 99%
“…Following a review of the titles and abstracts, 187 studies were selected as potentially relevant, and their references were cross-checked. Thirty-three publications eventually fulfilled the inclusion criteria and were selected for quantitative synthesis (Table 2) [26,27,30,42,44,. The flow chart of the selection process is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The hypermetabolic activity of PMs increases their conspicuity using FDG PET/CT. CT and FDG PET/CT are considered equivalent alternatives for the detection of recurrent OC [1, 17,30,[36][37][38][39][40][41][42][43][44]. Based on the results of a recently published meta-analysis, FDG PET/CT had high diagnostic accuracy, with 88% sensitivity and 89% specificity in the detection of recurrent OC [45].…”
Section: Ar3mentioning
confidence: 99%
“…The study of Schmidt et al 21 showed that [ 18 F]FDG PET/CT had the highest specificity for the detection of peritoneal carcinomatosis in ovarian cancer compared with multidetector CT and MRI, and whole‐body FDG PET/CT may be more accurate for the detection of supradiaphragmatic metastases. Mallet et al 22 indicated that [ 18 F]FDG PET/CT metabolic parameters were highly accurate in predicting peritoneal metastases, and [ 18 F]FDG PET/CT improved the detection of extra‐abdominal lesions, leading to treatment modification in a significant proportion of patients compared with CT. Van ‘t Sant et al 23 found that PET/CT and (DW)MRI had a comparable overall diagnostic value in detecting peritoneal metastases. Rubini et al 24 reported that the sensitivity, specificity and accuracy of [ 18 F]FDG PET/CT in the identification of peritoneal carcinomatosis in patients with ovarian cancer were 78.6%, 91.3% and 84.3%, respectively; for CT with contrast enhancement (CECT), they were 53.6%, 60.9% and 56.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%